MAKNA PADA TEKS DESAIN KEMASAN JAMU KHUSUS WANITA - Listia Natadjaja; Faruk Tripoli; Bayu Wahyono (Fakultas Sastra Universitas Negeri Malang, 2014)
The study examined the meanings of the texts on the packaging of jamu for women and revealed its proposed ideology. As a health product, information on the design of the packaging of jamu is not only as a means to inform consumers of the product, but also as a